The Effect of Mn and Ti Ratio on Microstructure and Mechanical and Machinability Properties of 316 L Stainless Steel Used in Biomedical Applications - Mustafa Türkmen; Alla Muhammed Tanouz; Mahir Akgün; Mehmet Akif Erden (Metals, 2023)
In this study, titanium (Ti) and manganese (Mn) element powders in determined amounts (0.35–0.75 and 1.5 wt %) were added into the 316 L stainless steel matrix by means of powder metallurgy (PM) technology, either individually or in pairs, and the desired composition was obtained as a powder mixture. The powders used in the study were cold-pressed tensile sample molds prepared in ASTM E8M standards, unidirectionally cold-pressed under 750 MPa compression pressure and formed into blocks. After pressing, the raw strength samples were sintered in an atmosphere-controlled tube furnace at 1250 °C for two hours in an argon atmosphere. The microstructure and mechanical properties of the produced PM steels were characterized using an optical microscope, SEM, EDS, tensile test, and hardness test. The results showed that the stainless steel samples with 0.35 (Ti and Mn) added to 316 L stainless steel had the highest yield strength, tensile strengths, and hardness strengths. However, with the addition of 0.75–1.5 Ti, 0.75–1.5 Mn and 0.75–1.5 (Ti and Mn) to 316 L stainless steel, a decrease was observed in the mechanical properties. Moreover, the stainless steel sample with 0.35 (Ti and Mn) added to 316 L stainless steel is better than other samples in terms of surface quality.